The Portuguese version of Rhinitis and Asthma Patient's Perspective (RAPP): Validation and assessment - Todo-Bom, A.; Braido, F.; Molinengo, G.; Loureiro, C.; Canonica, G.W.; Baiardini, I. (Pulmonology, 2020)
Allergic rhinitis (AR) and asthma are two common chronic diseases that often coexist. There is a need for a validated tool to evaluate HRQoL of Portuguese speakers with asthma and/or rhinitis patients in clinical practice. To adapt and validate RhinAsthma Patient Perspective (RAPP) in Portuguese. The RAPP questionnaire was translated into Portuguese. Asthmatics with comorbidities and rhinitis attending the allergy department of Coimbra University Hospital were asked to complete the Portuguese translation of RAPP, in addition to the SF-12, ACT, and a Symptomatologic VAS twice, with a 4-week interval between visits. During Visit 2, a Global Rating Scale (GRS) was completed to assess any change in health status. Scale dimensions, internal consistency and convergent validity, reliability, discriminant ability and responsiveness to change, as well as Minimal Clinical Difference were assessed. Factor and confirmatory analysis confirm the unidimensional structure of the questionnaire. Internal consistency has been shown to be satisfactory (0.82 visit 1 and 0.86 at visit 2). The tool is able to discriminate between patients on the basis of asthma severity, asthma control level, and rhinitis severity; convergent validity showed a significant correlation with SF-2 Physical component (r=−0.46 and 0.42, p at Visits 1 and 2). An ICC of 0.97 and a CCC=0.94 indicate that the tool is highly reliable. Responsiveness was shown in detecting a significant association with GRS changes (r=0.41, p<0.01) and ACT (r=−0.47, p<0.01) but not with VAS. (r=.14, n.s.). MID value was 2 points. The Portuguese version of RAPP has been demonstrated to have good measurement properties and sensitivity to health changes, which will provide a valid, reliable and standardized HRQoL measurement in patients with asthma and comorbid allergic rhinitis in clinical practice.